2013
DOI: 10.1016/j.jacc.2013.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Polymer Biolimus-Eluting Stent Versus Durable Polymer Everolimus-Eluting Stent

Abstract: One-year clinical and angiographic outcome after BES implantation was noninferior to and not different from that after EES implantation in a mostly stable coronary artery disease population. One-year clinical outcome after both BES and EES use was excellent, with a low rate of TLR and extremely low rate of stent thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
123
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 194 publications
(138 citation statements)
references
References 8 publications
8
123
2
Order By: Relevance
“…The NEXT trial reported that one-year clinical outcome after implantation of both biolimus-eluting stent and everolimus-eluting stent was phenomenal, with a low rate of TLR and stent thrombosis [20]. Along with NEXT trial, the NOBORI 2 study also concluded good and sustained performance of biodegradable polymers in high-risk patients with indicative comorbidities and/or complex lesions [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NEXT trial reported that one-year clinical outcome after implantation of both biolimus-eluting stent and everolimus-eluting stent was phenomenal, with a low rate of TLR and stent thrombosis [20]. Along with NEXT trial, the NOBORI 2 study also concluded good and sustained performance of biodegradable polymers in high-risk patients with indicative comorbidities and/or complex lesions [21].…”
Section: Discussionmentioning
confidence: 99%
“…Along with NEXT trial, the NOBORI 2 study also concluded good and sustained performance of biodegradable polymers in high-risk patients with indicative comorbidities and/or complex lesions [21]. Moreover, the safety and performance of biodegradable polymers with limus family of DES were firmly accepted in a real-world patient population [17] [20]. In this study, we collected and analyzed the data of Metafor SES with the perspective to evaluate the safety and performance of Metafor SES.…”
Section: Discussionmentioning
confidence: 99%
“…In the COMPARE II trial, biodegradable polymer biolimus-eluting stents proved non-inferior in direct comparison with durable polymer EES with respect to a composite of cardiac death, myocardial infarction and clinically-indicated target vessel revascularization at one year (12). Similarly, the NEXT trial demonstrated no significant differences between biolimus-eluting stents with a biodegradable polymer and EES with a durable polymer with regard to the primary efficacy endpoint target lesion revascularization at one year (13). Of note, all biodegradable polymer stents used in the trials mentioned above were based on stainless steel platforms with a strut thickness comparable to early generation DES and have not been combined with newer generation metallic platforms.…”
Section: Introductionmentioning
confidence: 99%
“…The designs and the 3‐year clinical outcomes of RESET and NEXT have been previously described in detail 5, 6, 7. In short, both RESET and NEXT are prospective, multicenter, randomized “DES versus DES” trials, in which eligible patients were randomly assigned to undergo percutaneous coronary intervention (PCI) with either everolimus‐eluting stents (EES; Xience V, Abbott Vascular, CA/PROMUS, Boston Scientific, MA) or sirolimus‐eluting stents (Cypher/Cypher select/Cypher Select‐plus; Cordis Corporation, Johnson and Johnson, NJ) in the RESET, and with either biolimus‐eluting stents (Nobori, Terumo, Tokyo) or EES in the NEXT.…”
Section: Methodsmentioning
confidence: 99%
“…Qualitative and quantitative coronary angiography (QCA) were assessed utilizing CAAS 5.9 (Pie Medical Imaging, Maastricht, Netherlands). Details of the angiographic analysis were previously presented 5, 6. In a subset of patients enrolled in the angiographic substudy, follow‐up angiography was performed between 240 and 365 days after the index PCI procedure in both the RESET and NEXT trials 7.…”
Section: Methodsmentioning
confidence: 99%